Predicting Deterioration in Patients With Normotensive Acute Pulmonary Embolism Using Clinical‐Imaging Features: A Multicenter Prospective Cohort Study - Yizhuo Gao; Shibo Wei; Yuchen Liu; Zhenglun Yu; Shanshan Zhan; Binze Yang; Chuanxin Qi; Shougang Qi; Minggang Wang; Dong Jia (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Prioritization of management strategies in patients with normotensive acute pulmonary embolism is based on the identification of individuals at risk for early deterioration. This study aims to develop and validate a novel score for deterioration prediction using clinical‐imaging features. Methods This is multicenter, prospective observational cohort study (AOAPECT [Adverse Outcomes in Acute Pulmonary Embolism patients using Computed Tomography pulmonary angiography] cohort, NCT05098769). Registered‐enrolled patients with normotensive acute pulmonary embolism were collected consecutively from 5 centers across China. Derivation set was established from 2 centers, while local and nonlocal external validation sets were derived from the remaining 3 centers. The end point was pulmonary embolism‐related deterioration within 30 days after admission. Deterioration‐related candidate predictors consisted of clinical, laboratory and computed tomography pulmonary angiography parameters were screened and then split into dichotomous values. The predictive score was conducted by a multivariable logistics regression and validated. Score performances were quantified using the area under the receiver operating characteristic curve. Results Of 3310 enrolled patients including 1 derivation (n=2061) and 2 validation sets (n=969 and 280), 272 patients (8.2%) experienced deterioration. In the derivation set, an increased risk of deterioration was observed with right to left ventricle diameter ratio ≥1.2, appearance of pulmonary vein sign on computed tomography pulmonary angiography, and heart rate ≥110 beats/min. When at least 2 out of 3 items were positive, patients were assigned to the high‐risk deterioration group. This PE‐RPH score revealed good discrimination to deterioration in derivation and validation sets (area under the receiver operating characteristic curve, 0.82, 0.82, and 0.80). Conclusions This PE‐RPH score incorporating 2 computed tomography pulmonary angiography parameters and heart rate may help predict the deterioration risk in patients with normotensive acute pulmonary embolism. REGISTRATION: https://clinicaltrials.gov; identifier: NCT05098769.